A public health advocacy approach for preventing and reducing gambling related harm - Jennifer L. David; Samantha L. Thomas; Melanie Randle; Mike Daube (Elsevier, 2020)
Abstract Objective: To develop a framework to guide the application of public health advocacy strategies aimed at preventing and reducing gambling‐related harm. Methods: A narrative review of theories of change and public health advocacy literature. Results: An eight‐step public health advocacy framework was created, which outlines the critical steps and considerations when developing and implementing successful change efforts. Implications for public health: To date, a clear public health advocacy approach to gambling harm prevention and reduction has not been well established. This study proposes a gambling‐specific framework to guide future public health advocacy efforts to prevent and reduce gambling harm.